Income inequality and the composition of public debt. Issue 5 (12th October 2015) - Salti, Nisreen
Abstract : Purpose: – The purpose of this paper is to examine the redistributive effect of domestic public debt: lenders to the government lie on the higher end of the income distribution, but the burden of debt financing falls on the entire tax base, to the extent that taxes are used to service debt. Because domestic debt is typically held by domestic lenders, this involves a redistribution of resources. Design/methodology/approach: – The author uses cross-country panel data on debt composition, and run regressions of income inequality, as measured by the Gini coefficient, using various specifications, controlling for a variety of macroeconomic, fiscal and political variables. Findings: – The author finds that the composition of public debt is consistently a significant determinant of income inequality: the domestic share of public debt is regressive and significant across all specifications, even controlling for total and external debt servicing, political conflict, corruption and a variety of government spending variables. Research limitations/implications: – The data span 18 years (1990-2007) which means that long-run effects are hard to track. While the author has a good mix in the sample of observations from low-, middle- and high-income countries, the author is constrained in the choice of countries by the availability of data on inequality and on the composition of public debt. Originality/value: – This is the first paper to examine the composition of public debt in terms of domestic and external debt, and any bearing it may have on income inequality. The finding is also new for both the public debt and income inequality literatures: cross-country panel data are consistent with the belief that domestic debt redistributes resources from the entire tax base to wealthy holders of government debt in a way that external debt does not.